1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Prove the mean of the weibull distribution

  1. Nov 2, 2012 #1
    1. The problem statement, all variables and given/known data
    This is the full question, but we're only asked to do b.

    A random variable x has a Weibull Distribution if and only if its probability density is given by f(x) = {kx^(b-a) *exp(-ax^b) for x > 0 }
    where a and b > 0.

    a) Express k in terms of a and b.
    b) Show that u = a^(-1/b) * gamma(1 + 1/b)

    2. Relevant equations

    All of the following could be of use.
    Mx(t) = ∫exp(xt)f(x) dx
    and the limit as t → 0 of M'x(t) = u = mean
    u = Ex(x) = ∫xf(x)dx
    gamma(a) = ∫x^(1-a)exp(-x)dx

    Also the integral of f(x) = 1.

    3. The attempt at a solution

    I tried making a substitution for x, so that I could get the gamma function out of the integral, but that x^b really throws me.

    I tried integrating by parts, but that just gives an even more complicated expression. I wanted to get rid of part of the equation by setting it to one, but no matter how you treat it you'll have a nasty exp(-ax^b) to deal with.

    There's obviously some trick I'm supposed to use to figure it out.

    Can anyone provide any hints? I've spent a good couple hours both trying to solve it and googling similar solutions.
  2. jcsd
  3. Nov 3, 2012 #2
    Bumping back to first page.
  4. Nov 4, 2012 #3


    User Avatar
    Science Advisor
    Homework Helper
    Gold Member

    What substitution did you try? What is the obvious one to get rid of the power within the exponential?
  5. Nov 4, 2012 #4
    Not sure why, but it's not letting me edit the first post.

    It should be kx^(b-1) *exp(-ax^b) not ∫kx^(b-a) *exp(-ax^b), but anyway, I took another crack at it and I solved it!

    u = ax^b
    du = abx^(b-1) dx

    ∫kx^(b-1) *exp(-ax^b) dx
    = k/(ab)∫exp(-u) du
    = k/ab[1] = 1, so k = ab.

    ∫kx^(b) *exp(-ax^b) dx
    = k∫x^(b) *exp(-ax^b) dx
    = k/(ab)∫(u/a)^(1/b) exp(-u)du
    = a^(-1/b)k/(ab) ∫u^(1/b) exp(-u) du
    = a^(-1/b-1)k/b Γ(1/b + 1)
    sub k = ab in and you get
    =a^(-1/b)Γ(1/b + 1)

    Thanks a lot! I guess I just needed to know that substitution was the method to solve it for me to be able to do the math.
    Last edited: Nov 4, 2012
  6. Nov 4, 2012 #5


    User Avatar
    Science Advisor
    Homework Helper
    Gold Member

    Good show.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook